The Impact of the Euro on New EU Member States During the Economic Crisis - Mrázek, Jan (2014)
The goal of this thesis is to analyze the development of several macroeconomic and financial indicators over the course of eight years for the countries that joined the European Union after the year 2000. The indicators' development will then be investigated to discern the impacts the Euro had on it during the recent economic crisis. The analysis of the data has revealed no evidence that would support the claim that the Euro would have any significant impact -- beneficial or detrimental -- during the crisis on the countries that have adopted it. The observed development of the indicators had different causes than what currency the particular country used as its legal tender.